Analyzing the Relationships Between Business Conditions and Happiness in OECD Countries: Application of the fsQCA Method - Choi, Young-Chool (International Journal of Engineering and Technology, 2019)
This paper aims to identify the configurations of business conditions affecting happiness in 35 OECD member countries, using as a basis the assumption that happiness at the national level can be affected by the conditions for business activities, which can be defined as the conditions under which workers carry out their business to make a living. To achieve the research goal, the paper employs Fuzzy-set Qualitative Comparative Analysis (fsQCA) as a research methodology. This research method has rarely been used in the analysis of happiness conditions. For this analysis, five independent variables and one dependent variable are used. The countries analysed are 35 OECD member countries. The results show that four configurations of business conditions affect happiness at the national level in these countries. This implies that each country whose happiness level is relatively low needs to benchmark that of the four configurations which it considers relates most closely to or has featured in common with, its own business conditions. In other words, because there are plural options for producing happiness in countries at the national level, each country with low levels in terms of happiness can benchmark or follow countries with this same configuration, leading to high levels of happiness.Â